Quality of breakfast sausage containing legume flours as binders (2013)
The effects of different legume flours, viz., soybean, groundnut and cowpea flour, on the quality of breakfast sausage was studied. The study comprised of four treatments, treatment one with sodium caseinate served as the control while the remaining treatments contained soybean, groundnut and cowpea flour at 4% inclusion level respectively. Each treatment was replicated four times in a completely randomized design. Sausage with sodium caseinate had the highest (P<0.05) yield (92.20%), this was followed by products with cowpea (89.14%), soybean (89.00%) however, the least was obtained with product containing groundnut (80.02%). Sausage samples containing groundnut flour lost an average weight of 28.10% during cooking (P<0.05) whilst those containing sodium caseinate, soybean and cowpea flour lost an average weight of 20.91, 21.31and 21.44 % respectively. The water holding capacity of sodium caseinate products increased significantly compared to that of soybean (70.75%) and cowpea flour (69.34%) while the least was observed in products containing groundnut flour. Formulations with soybean flour registered higher thiobarbituric acid values (mg malonaldehyde/kg sample) of 0.75 as against 0.57, 0.52 and 0.51 for formulations with cowpea flour, sodium caseinate and groundnut flour respectively. Sausage with soybean flour had higher (P<0.05) overall acceptability (6.30) than products with sodium caseinate (5.50), groundnut (5.10) and cowpea (4.00). However, sausage with cowpea flour had similar (P>0.05) moisture content (79.50%) with sausage that contained soybean flour (80.24%) while the highest (P<0.05) crude protein content was in treatment with sodium caseinate (19.50%) and least in sausage with cowpea flour (15.55%). The fat content was highest (P<0.05) in sausage with cowpea flour (15.35%), followed by 13.35% for sausage with soybean flour, 11.10 for formulation with groundnut flour and 10.25% for those with sodium caseinate. The quality attributes in terms of nutrient, flavour, juiciness and tenderness were better in sausage with soybean flour compared to sausage produced using other legume flours.